Antibacterial Food Packaging with Chitosan and Cellulose Blends for Food Preservation - Qu, Tengfei; Wang, Xiaowen; Zhang, Fengchun (Polymers, 2025)
With the increasing demand for food quality and the need for green and sustainable development of food packaging materials in the environment, the preparation and optimization of multifunctional natural and renewable antibacterial packaging materials have become an important trend. This article aims to explore the development of chitosan–cellulose composite materials with good antibacterial properties and promote the widespread application of chitosan and cellulose in food packaging materials. Combining various natural polysaccharide polymers, we discuss the application of chitosan cellulose in meat, dairy products, fruits and vegetables, and fishery products. Meanwhile, we explore their antibacterial and antioxidant behaviors during their use as food packaging materials. This provides a reference for effectively improving the performance of modified chitosan and cellulose food packaging materials in the future. Based on the above explanation, we analyzed the advantages and disadvantages of modified chitosan and cellulose and looked forward to the future development trends of chitosan and cellulose blend films in food preservation. Chitosan–cellulose blends not only have important prospects in food packaging and preservation applications, but can also be combined with intelligent manufacturing to enhance their food preservation performance. The aim of this review is to provide valuable references for basic research on the antimicrobial properties of these composites and their practical application in smart food packaging.